First Nations, Inuit, and Métis Women's Experiences of Cancer Survivorship: Protocol for the National Picture Project. Issue 1 (February 2015) - Thomas, Roanne; Gifford, Wendy; Poudrier, Jennifer; Hamilton, Ryan; Brooks, Carolyn; Scott, Tracy; Morrison, Tricia; Warner, Doris; Hammond, Chad
Little is known about First Nations, Inuit, and Métis (FNIM) women's experiences with cancer, including how they relate to cultural and social factors such as geography, history, racism, identity, traditional values/practices, and spirituality. Research into FNIM women's strengths and challenges in relation to cancer is much needed. Our team, in partnership with Saint Elizabeth Health, is documenting the experiences and needs of 60 FNIM cancer survivors across Canada, using sharing sessions, photography (photovoice), journaling, and film. We will evaluate the impact of photography and journaling on the participants to assist with the future development of supportive programs and health- care delivery. This innovative research will result in a video, which will address gaps in knowledge and care. The video will then be screened in several communities and will be publicly available. In future projects, the findings and video will be used in supportive programs for cancer survivors and in educational initiatives for health professionals.